Effects of electroacupuncture on dry eye: A pilot randomized controlled trial. Issue 3 (17th October 2022) - Yang, Guang; Kong, Xiehe; Guo, Xiaocong; Yang, Yanting; Xie, Chen; Lu, Yunqiong; Liu, Jie; Wu, Huangan; Zhang, Dan; Zou, Yuelan; Zhang, Cuihong; Hong, Jue; et al.
Abstract: Purpose: The purpose of the study was to assess the efficacy of electroacupuncture on dry eye (DE). Methods: Eighty‐four DE patients were randomly assigned to receive electroacupuncture (EAG) three times a week or 0.1% sodium hyaluronate artificial tears (ATG) four times per day for 4 weeks. The primary outcomes were non‐invasive tear film breakup time (NIBUT) and tear meniscus height (TMH). The secondary outcomes included the ocular surface disease index (OSDI), Schirmer I test (SIT), corneal sodium fluorescein staining (CFS) score, corneal topography descriptors surface asymmetry index (SAI) and surface regularity index (SRI), corneal sensitivity, 36‐item Short‐form Health Survey (SF‐36) score and Hospital Anxiety and Depression Scale (HADS) score. All outcomes were assessed at Week 0 (baseline), Week 4 (after‐treatment) and Week 8 (follow‐up). Results: Between‐group comparisons showed significant differences in the changes in NIBUT (Week 4, p  = 0.003; Week 8, p  = 0.008), TMH (Week 4, p  = 0.014; Week 8, p  = 0.009), OSDI (Week 4, p  = 0.029; Week 8, p  = 0.022), CFS score (Week 8, p  = 0.036) and SF‐36 role‐physical score (Week 4, p  = 0.010), favouring EAG. Mean changes in SIT, SAI, SRI, corneal sensitivity and HADS scores were statistically equal between the two groups (all p  > 0.05). Treatment with electroacupuncture was well‐tolerated and showed minimal adverse events. Conclusions: Compared with artificial tears, electroacupuncture shows superior efficacy in improving tear film stability and symptoms of DE.